Efficacy and safety of combined treatment of acute rhinosinusitis by herbal medicinal product Sinupret and mometasone furoate nasal spray - Perić, Aleksandar; Vezmar Kovačević, Sandra; Gaćeša, Dejan; V. Perić, Aneta (ENT Updates, 2017)
Objective: Herbal medicinal products have a well-established role in therapy of upper airway inflammations. Current evidence supports the use of intranasal corticosteroids for improvement in clinical symptoms of uncomplicated acute rhinosinusitis (ARS). We aimed to evaluate efficacy and safety of combined therapy by mometasone furoate nasal spray (MFNS) and oral herbal medicinal product Sinupret in comparison to MFNS monotherapy when treating mild to moderate ARS. Methods: Forty-six ARS patients were divided into two groups. Group 1 (n=23) received herbal drug Sinupret, 160 mg per os, three times daily and MFNS 200 μg twice daily for 7 days. Group 2 (n=23) received only MFNS 200 μg twice daily for 7 days. We assessed total symptom score (TSS), individual symptom scores for each symptom (nasal obstruction, rhinorrhea, postnasal drip, facial pain/pressure, impaired sense of smell) and endoscopic findings (mucosal edema, mucopurulent secretion), before and after treatment. Results: Significant improvement of all clinical parameters was found after both treatment modalities (p<0.000). We observed lower post-treatment TSS (p=0.002), nasal obstruction (p=0.001), rhinorrhea (p=0.001), facial pain (p=0.001), impaired sense of smell (p=0.002), mucosal edema (p=0.003) and mucopurulent secretion (p=0.001) in MFNS/Sinupret group than in MFNS group. We found no adverse events in MFNS/Sinupret group, while only 1 patient reported mild epistaxis and 1 patient reported dryness in the nose in MFNS Group. Conclusion: Our results suggest better efficacy of combined MFNS/Sinupret therapy of ARS on nasal symptoms and endoscopic findings, with the absence of adverse events in comparison to MFNS monotherapy.